ChemInform Abstract: C—H Functionalization of Cyclic Amines: Redox‐Annulations with α, β‐Unsaturated Carbonyl Compounds. Issue 44 (15th October 2015) - Kang, YoungKu; Richers, Matthew T.; Sawicki, Conrad H.; Seidel, Daniel
Abstract The redox‐annulation of pyrrolidine (II) with unsaturated ketones (I) gives rise to fused pyrrolines (III), which are converted into pyrroles and pyrrolidines.